2015
DOI: 10.1038/nchem.2400
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the leaving group on the dynamics of a gas-phase SN2 reaction

Abstract: In addition to the nucleophile and solvent, the leaving group has a significant influence on SN2 nucleophilic substitution reactions. Its role is frequently discussed with respect to reactivity, but its influence on the reaction dynamics remains unclear. Here, we uncover the influence of the leaving group on the gas-phase dynamics of SN2 reactions in a combined approach of crossed-beam imaging and dynamics simulations. We have studied the reaction F(-) + CH3Cl and compared it to F(-) + CH3I. For the two leavin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
198
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(212 citation statements)
references
References 34 publications
10
198
1
3
Order By: Relevance
“…As shown in the figure, the methyl group rotates around the iodine ion before moving to the chloride ion. Note that the significance of the "Min1" complex is suggested in a recent study using a dynamics simulation [20].…”
Section: Reaction Path Search For CLmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in the figure, the methyl group rotates around the iodine ion before moving to the chloride ion. Note that the significance of the "Min1" complex is suggested in a recent study using a dynamics simulation [20].…”
Section: Reaction Path Search For CLmentioning
confidence: 99%
“…Moreover, they suggested the significance of a double-inversion mechanism, in which the hydrogen atom of the methyl group first moves to F − and the methyl group then transfers to F − [19]. Comparing the results of a cross-beam imaging experiment with the dynamics simulation calculation, they, however, found that the mechanism significantly depends on the leaving group, which is X of the F − + CH 3 X → CH 3 F + X − reaction (X = Cl or I) [20]. Based on the above-mentioned orbital energy-based reaction analysis, it is recently found that two S N 2 reactions, F − + CH 3 Cl → Cl − + CH 3 F and OHCH 3 + F − → OH − + CH 3 F reactions, are also expected to avoid the minimum energy paths because these reactions give large reactivity indices indicating structural change-driven processes for the initial processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bimolecular nucleophilic substitution (S N 2) reaction is the most common reaction of that type, in which a nucleophile (often negatively charged) approaches a saturated carbon from one side, displaces a leaving group on the opposite side of the carbon atom, resulting in inversion of the carbon centre. Strong solvent effects of these reactions in solution have prompted investigations of the gas-phase S N 2 reaction to probe the intrinsic reaction mechanisms without solvent123456789101112131415161718192021222324252627. Numerous experimental and theoretical studies have revealed that an inverse secondary kinetic isotope effect (KIE), that is, k H / k D <1 (where k denotes the thermal rate constant), is characteristic for a thermal S N 2 reaction when the isotopically substituted atom is not directly involved in a reaction12345678910.…”
mentioning
confidence: 99%
“…Many reduced dimensionality quantum scattering studies were also carried out to investigate dynamics in S N 2 reactions19202122. Recently, the molecular beam experiments in the Wester's group, in combination with theory, have revealed unprecedented dynamical details on some exothermic S N 2 reactions2324252627. However, despite so many experimental and theoretical investigations, the origin of the intriguing difference between the isotope effects on the kinetic and cross-sections as well as the high-energy threshold for centre barrier and endothermic S N 2 reactions remain unclear.…”
mentioning
confidence: 99%